The delivery mechanism system of microcredit program and micro enterprise performance / Wan Rasyidah Wan Mohamed - Wan Mohamed, Wan Rasyidah (2019)
The research is to study the delivery mechanism system and the performances of the microenterprise in Kelantan. The study used primary data collected from a total of 161 respondents who are involved in microenterprise and currently used micro financing services under Amanah Ikhtiar Malaysia. The objective of the study is to examine the relationship between modes of financing, operational efficiency, entrepreneurship development and monitoring and supervision with the micro enterprises performance and to improve the delivery mechanism of microcredit programs. The previous study by Mahmood and Mohd Rosli (2013) and Mahmood et al (2015) shows a positive relationship between modes of financing, operational efficiency, entrepreneurship development and monitoring and supervision. Using a multiple regression method the result show that operational efficiency, entrepreneurship development and monitoring and supervision are significant at p < 0.01. Meanwhile modes of financing is not significant with the business performances and not consistent with previous findings in the literature review.